Motivation of Young Generation to Create A Generation of Excellent Achievement and Character in Lampung Province - Sahrul Ari Irawan; M. Ilham Pu’adi; Serly Silviyanti; Tyas Sekartiara Syafani; Herman Herman (International Journal of Social Service and Research (IJSSR), 2023)
The low sense of enthusiasm in the work of the younger generation makes the next generation of the nation will be hindered from achieving their goals in the future.  Various factors make it difficult for the younger generation to work and find their identity by finding and honing their life skills.  The current globalization and the lack of love for reading and writing literacy are one of the biggest causes for the younger generation to find it difficult to achieve a generation of excellence, achievement, and character.  The purpose of this study is to find out the efforts that can be made to increase the enthusiasm of the younger generation and to know the efforts that can be made to compile and achieve success tips in achieving goals for a better generation.  This research was conducted by a survey of the younger generation in Lampung Province with a qualitative approach, in terms of literature study analysis or case study.  Research has conducted in 35 locations consisting of schools, organizations, Islamic boarding schools, and groups of youth communities (young generation).  The result of this study is that the usual motivation to raise enthusiasm or motivation is to apply the friendship facilitator method, achievement motivation training (AMT), and Training Within Industry (TWI).  Success tips that can arouse the enthusiasm of the younger generation to achieve their goals are to record plans and set goals, always believe in abilities, always thirst for experience and knowledge, network, and maintain self-optimism.